NADPH Oxidase 2-Mediated Insult in the Auditory Cortex of Zucker Diabetic Fatty Rats. (30th July 2019) - Du, Zheng-De; Wei, Wei; Yu, Shukui; Song, Qing-Ling; Liu, Ke; Gong, Shu-Sheng
Abstract : Clinical data has confirmed that auditory impairment may be a secondary symptom of type 2 diabetes mellitus (T2DM). However, mechanisms underlying pathologic changes that occur in the auditory system, especially in the central auditory system (CAS), remain poorly understood. In this study, Zucker diabetic fatty (ZDF) rats were used as a T2DM rat model to observe ultrastructural alterations in the auditory cortex and investigate possible mechanisms underlying CAS damage in T2DM. The auditory brainstem response (ABR) of ZDF rats was found to be markedly elevated in low (8 kHz) and high (32 kHz) frequencies. Protein expression of NADPH oxidase 2 (NOX2) and its matching subunits P22 phox, P47 phox, and P67 phox was increased in the auditory cortex of ZDF rats. Expression of 8-hydroxy-2-deoxyguanosine (8-OHdG), a marker of DNA oxidative damage, was also increased in the neuronal mitochondria of the auditory cortex of ZDF rats. Additionally, decreases in the mitochondrial total antioxidant capabilities (T-AOC), adenosine triphosphate (ATP) production, and mitochondrial membrane potential (MMP) were detected in the auditory cortex of ZDF rats, suggesting mitochondrial dysfunction. Transmission electron microscopy results indicated that ultrastructural damage had occurred to neurovascular units and mitochondria in the auditory cortex of ZDF rats. Furthermore, cytochrome c (Cyt c) translocation from mitochondria to cytoplasm and caspase 3-dependent apoptosis were also detected in the auditory cortex of ZDF rats. Consequently, the study demonstrated that T2DM may cause morphological damage to the CAS and that NOX2-associated mitochondrial oxidative damage and apoptosis may be partly responsible for this insult.